Chaotic Fractional Order Delayed Cellular Neural Network - Celik, Vedat; Demir, Yakup (Springer-Verlag Berlin, 2010)
This paper deals with the fractional order model of the two-cell autonomous Delayed Cellular Neural Network which exhibits chaotic behavior. Numerical simulation results demonstrate that the chaos can be observed in fractional order Delayed Cellular Neural Network for fractional order q >= 0.1. Also the tau delay time values for which the chaos occurs in q system order, is quantitatively defined using largest Lyapunov exponents.
International Workshops on New Trends in Science and Technology (NTST 08)/ Fractional Differentiation and its Applications (FDA08) -- NOV, 2008 -- Cankaya Univ, Ankara, TURKEY
Keywords: System